BIONIC PRINCIPLES IN ARCHITECTURE AND DESIGN - Krizhanivskiy, Oleksandr; Spivak, Iryna (Theory and practice of design, 2023)
Purpose. Consider the issue of using bionic principles in the architecture and design of the modern environment and interior. Methodology. It consists in the analysis of practical construction experience using bionic principles and the generalization and systematization of domestic and foreign experience. Results. The article emphasizes that one of the main tasks of modern times is the protection of the environment, so architects and designers have developed a bionic style that helps to solve environmental problems of modern times. The authors revealed the history, philosophy and achievements of bionics in design, architecture and other fields. The features of the use of bionic principles in architecture and interior design were described. Scientific novelty. The prospects of using modern constructive and construction technologies are revealed. Examples of bionic design solutions that can be found in ordinary residential complexes and modern interiors are given. Practical relevance. One of the ways to avoid environmental problems is the active application of bionic principles in architecture, planning, construction and design.